2020
DOI: 10.18203/2320-1770.ijrcog20203993
|View full text |Cite
|
Sign up to set email alerts
|

Study of maternal and fetal outcome in pregnancy beyond 40 weeks: a prospective observational study at a tertiary institute

Abstract: Background: Prolonged pregnancy is one that exceeds 42 0/7weeks. Management of prolonged pregnancy is very challenging in modern obstetrics.Methods: It is prospective observational study in department of Obstetrics and Gynecology, Shri B.M Patil medical college and Research center, deemed to be University, Vijayapur, North karnataka. Study period was from January 2018 to January 2019.Results: Total of 186 pregnant women were included in the study. Results in terms of age, gravidity, gestational age, time of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…3 Another study done in Karnataka, India showed that 32% had undergone caesarean section. 9 Similar to the findings, a study done in Uttar Pradesh, India also showed that 42.30% had caesarean section while remaining 57.7% had normal vaginal delivery. 8 In the present study, indications for caesarean section was fetal distress in 53.3% mothers, non-progress of labor in 13.3 % cases, cephalopelvic disproportion in 10% cases, severe oligohydramnios in 11.6% cases and failure of induction in 11.6% mothers.The indications of caesarean section in the study is similar with a study done in Dr. Ram Manohar Lohia Institute of Medical Sciences, Lucknow, where indication for caesarean section was meconium stained liquor with fetal distress in (26%) cases, failure of induction in (21%) cases , cephalo-pelvic disproportion in (16%) cases, severe oligohydramnios in (19%) and nonprogress of labor in (15%) cases.…”
Section: Discussionsupporting
confidence: 78%
“…3 Another study done in Karnataka, India showed that 32% had undergone caesarean section. 9 Similar to the findings, a study done in Uttar Pradesh, India also showed that 42.30% had caesarean section while remaining 57.7% had normal vaginal delivery. 8 In the present study, indications for caesarean section was fetal distress in 53.3% mothers, non-progress of labor in 13.3 % cases, cephalopelvic disproportion in 10% cases, severe oligohydramnios in 11.6% cases and failure of induction in 11.6% mothers.The indications of caesarean section in the study is similar with a study done in Dr. Ram Manohar Lohia Institute of Medical Sciences, Lucknow, where indication for caesarean section was meconium stained liquor with fetal distress in (26%) cases, failure of induction in (21%) cases , cephalo-pelvic disproportion in (16%) cases, severe oligohydramnios in (19%) and nonprogress of labor in (15%) cases.…”
Section: Discussionsupporting
confidence: 78%